60.1k views
0 votes
Factorize. xy^2-y(x-z) -z​

User Suckgamony
by
4.9k points

2 Answers

1 vote

Answer:

The equation x

The equation x 2

The equation x 2 +xy+xz+yz can be factorised as follows:

The equation x 2 +xy+xz+yz can be factorised as follows:x

The equation x 2 +xy+xz+yz can be factorised as follows:x 2

The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x

The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2

The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)

The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)Hence, x

The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)Hence, x 2

The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)Hence, x 2 +xy+xz+yz=(x+z)(x+y)

User Mikael S
by
5.5k points
6 votes

Answer:

= (y-1) (xy-z)

Explanation:

First we expand them -

= xy^2 - xy - yz - z

= xy(y-1)-z(y-1)

= (y-1) (xy-z)

Hope this helped

User Iamkhush
by
5.9k points